Composite and method of manufacturing the same
The complex with a wood-resin intermediate layer and aluminum base achieves strong adhesion and structural stability, addressing the challenges of bonding wood and metal substrates, suitable for building materials and vehicle parts.
Patent Information
- Application Number
- JP2024116689
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-24
- Filing Date
- 2024-07-22
- Publication Date
- 2025-02-05
AI Technical Summary
Existing technologies face challenges in achieving excellent adhesion and structural stability in multilayer complexes involving wood and metal substrates, particularly in applications requiring a clear wood grain pattern and robust bonding.
A complex is developed with an intermediate layer composed of wood pieces or wooden plates impregnated with resin, bonded to an aluminum-containing base through a process involving acid treatment, shot blasting, or electrolytic etching to create overhangs, and a design layer, using resins like melamine, phenol, or urethane resins to enhance adhesion.
The solution results in a multilayer structure with excellent adhesiveness and structural stability, allowing for clear wood grain visibility and suitable use in building materials, furniture, and vehicle parts.
Smart Images

Figure 2025017343000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite body having an intermediate layer that has excellent adhesion between an aluminum-containing base and a decorative layer, and a method for producing the same. [Background technology]
[0002] A known technique for producing a wood-based molded product having a woody texture is to process logs, waste materials, or recycled materials of wood, which can be used sustainably, into powder, fibers, chips, etc., and then place them together with a resin or a precursor thereof in a mold cavity and perform compression molding under heated conditions. Such a wood-based molded product is integrated with a base material made of metal or the like as necessary to produce a composite material, which is used for vehicle interior materials, fixtures such as furniture, building materials such as flooring materials, and wall materials.
[0003] The following techniques are known as composites having a woody texture or methods for producing the same. Patent Document 1 discloses a wood veneer board in which a fiber-reinforced synthetic resin layer having small pieces of wood dispersed therein is provided on one side of a metal substrate, a coating film made of unsaturated polyester resin is provided on the fiber-reinforced synthetic resin layer, and a fiber-reinforced synthetic resin layer is provided on the other side of the metal substrate. Patent Document 1 also discloses a method for producing a wood veneer board in which a metal substrate is placed on a fiber substrate impregnated with uncured synthetic resin, a composite substrate having small pieces of wood dispersed in the reinforcing fiber substrate impregnated with uncured synthetic resin is placed on the metal substrate, and the substrate is heated and pressurized to cure the resin and obtain an integrated product, and then an unsaturated polyester resin paint is applied to the integrated composite substrate. Patent Document 2 discloses a method for producing a composite material in which highly flexible synthetic resin is impregnated into wood by reducing pressure or applying reduced pressure under pressure, and then the impregnated resin is layered on a backing material without the use of adhesive while still in an uncured state, and curved and punched while being heated, so that the synthetic resin impregnated into the wood reacts and hardens, while at the same time the resin that has flowed out from within the wood bonds it to the backing material, thereby producing a composite material.
[0004] Patent Document 3 discloses a joining member in which a wood-based material and a non-wood-based material having recesses and / or protrusions on its surface are joined and integrated, characterized in that the wood-based material penetrates into and fills the recesses or around the protrusions of the non-wood-based material, with the relative positions of the wood fiber cells changed. Patent Document 4 also discloses a non-flammable wood composite material comprising a first wood material having a thickness in the range of 2-4 mm and containing a flame retardant agent, an inorganic substrate or a second wood material, and an adhesive layer interposed between the first wood material and the inorganic substrate or the second wood material, the flame retardant agent containing a first compound having a hydroxyl group, and the adhesive layer being made of an adhesive containing a second compound having a hydroxyl group or an aqueous material. Patent Document 4 also discloses a method for producing a non-flammable wood composite material by bonding a first wood material having a thickness in the range of 2-4 mm and containing a flame retardant agent to an inorganic substrate or a second wood material using an adhesive, the flame retardant agent containing a first compound having a hydroxyl group, the adhesive containing a second compound having a hydroxyl group or an aqueous material, and a method for producing a non-flammable wood composite material by forming an adhesive layer by hardening.
[0005] Incidentally, Patent Document 5 proposes surface modification of a metal substrate (forming an oxide film or expanding the surface area) to improve adhesion when an organic polymeric substance or the like is adhered to the surface of the metal substrate. Specifically, the method for treating a metal surface is characterized by comprising a first step of performing a chemical etching treatment accompanied by the formation of a film on the metal surface, and a second step of performing a treatment for chemically removing the film formed on the metal surface by the first step. Note that in Example 1 of Patent Document 1, an aluminum plate, which is a metal substrate, is also surface-treated in advance (a treatment for forming a chromium phosphate film) before the manufacture of a wood veneer board. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 3-239543 [Patent Document 2] Japanese Patent Application Publication No. 10-113906 [Patent Document 3] Patent Publication No. 2021-88059 [Patent Document 4] Patent Publication No. 2022-7386 [Patent Document 5] Japanese Patent Application Publication No. 11-293476 Summary of the Invention [Problem to be solved by the invention]
[0007] The object of the present invention is to provide a composite body having a base containing aluminum, an intermediate layer containing a wood material, and a decorative layer, which has excellent adhesion between the base and the intermediate layer, and between the decorative layer and the intermediate layer, and which has excellent structural stability as a multilayer body, and a method for manufacturing the same. [Means for solving the problem]
[0008] The inventors have discovered that by placing an assembly of resin-impregnated wood chips (chipped wood material) or a resin-impregnated wooden board on an aluminum-containing roughened substrate having an overhanging portion, and then placing a decorative material on top of that, and hot-pressing the resulting load, it is possible to obtain a composite comprising an aluminum-containing base, an intermediate layer derived from the above-mentioned assembly of resin-impregnated wood chips (chipped wood material) or resin-impregnated wooden board, and a decorative layer, which has excellent adhesion between the base and the intermediate layer and between the design layer and the intermediate layer, and which has excellent structural stability as a multilayer body.
[0009] The present invention is illustrated below. (1) A composite body consisting of an integrated body in which a base layer containing aluminum and a decorative layer are joined via an intermediate layer, A composite body, characterized in that the intermediate layer is made of an aggregate of resin-impregnated wood pieces or a resin-impregnated wood board, and the surface of the base on the intermediate layer side has a plurality of overhang portions. (2) The composite according to (1) above, wherein the resin is also contained within the cell walls of the wood pieces or wood boards. (3) The composite according to (1) above, wherein the resin is derived from at least one selected from the group consisting of melamine resin, phenolic resin, urea resin, acrylic resin, styrene-based resin and urethane resin. (4) The composite according to (1) above, wherein the intermediate layer has a thickness of 0.1 to 20 mm. (5) The composite according to (1) above, wherein the decorative layer comprises a thin body of wood. (6) The composite according to (1) above, wherein the overhang portion is formed by subjecting the surface of an article containing metallic aluminum or an aluminum alloy to an acid treatment, an electric discharge treatment, a shot blasting treatment, or an electrolytic etching treatment. (7) A method for producing the complex according to (1) above, comprising the steps of: A process of subjecting a substrate containing metallic aluminum or an aluminum alloy to an acid treatment, an electric discharge treatment, a shot blasting treatment, or an electrolytic etching treatment to form a plurality of overhang portions on a surface of the substrate, thereby producing an aluminum-containing roughened substrate; A step of crushing a resin component-impregnated wood obtained by impregnating wood with a resin component containing at least one selected from a precursor of a thermoplastic resin and a thermosetting resin to produce a resin component-containing crushed wood product; A step of placing the resin component-containing crushed wood material on a surface of the aluminum-containing roughened base material having the overhang portion to prepare a first load; A step of placing a design material on the resin component-containing crushed wood layer in the first load to prepare a second load; subjecting the second load to a hot press; A method for producing a composite comprising: (8) The method for producing a composite according to (7) above, wherein the thermoplastic resin is a urethane resin. (9) The method for producing a composite according to (7) above, wherein the thermosetting resin comprises at least one resin selected from the group consisting of melamine resin, phenolic resin, urea resin and urethane resin. (10) The method for producing a composite according to (7) above, wherein the resin component-containing crushed wood material has a major axis of 0.05 to 10 mm. (11) A method for producing the composite according to (1) above, comprising the steps of: A process of subjecting a substrate containing metallic aluminum or an aluminum alloy to an acid treatment, an electric discharge treatment, a shot blasting treatment, or an electrolytic etching treatment to form a plurality of overhang portions on a surface of the substrate, thereby producing an aluminum-containing roughened substrate; A step of producing a resin component-impregnated wooden board by impregnating a wooden board with a resin component containing at least one selected from a precursor of a thermoplastic resin and a thermosetting resin; A step of placing the resin component-impregnated wooden board on a surface of the aluminum-containing roughened base material having the overhang portion to prepare a third loaded object; A step of placing a design material on the resin component-impregnated wooden board in the third load to create a fourth load; subjecting the fourth load to a hot press; A method for producing a composite, comprising: (12) The method for producing a composite according to (11) above, wherein the thermoplastic resin is a urethane resin. (13) The method for producing a composite according to (11) above, wherein the thermosetting resin comprises at least one selected from the group consisting of melamine resin, phenolic resin and urea resin. (14) The method for producing a composite body according to (11) above, wherein the resin component-impregnated wooden board has a thickness of 0.01 to 20 mm. (15) The method for manufacturing a composite material according to (7) or (11) above, wherein the decorative material comprises a thin-walled body of wood. Effect of the Invention
[0010] According to the composite of the present invention, the adhesiveness between the aluminum-containing base and the intermediate layer, and the adhesiveness between the decorative layer and the intermediate layer are excellent, so that the structural stability of the multi-layer body is excellent. When the decorative layer is derived from wood, the composite body can have a clear wood grain. Since the base can be a support, the composite can be suitably used as building materials and architectural components, furniture and furnishings, vehicle components, home appliance parts, daily necessities, etc., which have excellent appearance due to the decorative layer. According to the method for producing a composite of the present invention, a composite exhibiting the above-mentioned effects can be efficiently produced. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic diagram showing a cross-sectional structure of a composite of the present invention. [Diagram 2] FIG. 2 is a schematic diagram illustrating a cross-sectional shape of an overhang portion formed on the surface of an intermediate layer side of an aluminum-containing base that constitutes the composite of the present invention. [Diagram 3] FIG. 2 is a schematic cross-sectional view showing an example of the outermost surface of an aluminum-containing roughened substrate used for producing the composite of the present invention. [Figure 4] 1 is a cross-sectional image showing the outermost surface of a pre-roughened metal aluminum plate before surface treatment in [Example]. [Diagram 5] 1 is a cross-sectional image showing the outermost surface of an acid-treated aluminum metal plate in [Example]. [Figure 6] 1 is a cross-sectional image showing the outermost surface of an aluminum alloy sheet (ADC12) that was acid-treated in [Example]. [Figure 7] 1 is a cross-sectional image showing the outermost surface of an aluminum alloy plate (AC4CH) that was acid-treated in [Example]. [Figure 8] 1 is a cross-sectional image showing the outermost surface of a metal aluminum plate subjected to electric discharge machining in the embodiment. [Figure 9] 1 is a cross-sectional image showing the outermost surface of an aluminum alloy plate (ADC12) that was shot blasted in [Example]. [Figure 10] 1 is a cross-sectional image showing the outermost surface of a metal aluminum plate sanded in [Example]. [Figure 11] 1 is an external appearance image of the composite obtained in Example 1. [Figure 12] 1 is a cross-sectional image of the composite obtained in Example 1. [Figure 13] 1 is an enlarged image of the interface between the base and middle layer of the composite obtained in Example 1. [Figure 14] 1 is an external appearance image of the composite obtained in Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The composite of the present invention is characterized in that it is made of an integrated body in which an aluminum-containing base and a decorative layer are joined via an intermediate layer, the intermediate layer being made of an assembly of resin-impregnated wood pieces or a resin-impregnated wooden board, and has a plurality of overhanging parts on the surface of the base on the intermediate layer side. Fig. 1 is a schematic diagram showing the cross-sectional structure of the composite 1 of the present invention, and although the overhanging parts are not shown, the surface of the base 2 is provided with an intermediate layer 4 and a decorative layer 6, in that order.
[0013] In the composite of the present invention, the base 2 including the overhang portion contains aluminum element, and is preferably mainly composed of metallic aluminum or an aluminum alloy, and the base 2 may further contain an aluminum compound such as aluminum oxide. The overhang portion and the remaining base main body portion may be made of different aluminum components.
[0014] The base 2 essentially acts as a support. The shape of the base 2 is not particularly limited, and may be a plate, a line (rod), a block, a ring, or the like, and may be a thin-walled body or a thick-walled body. In the present invention, the surface of the base 2 on the side of the intermediate layer 4 is provided with a plurality of overhanging parts, so that the surface of the base 2 is rough, but the overall surface of the base 2 is usually flat or uneven (including a wavy pattern and a jagged pattern).
[0015] The overhang portion according to the present invention has a shape that protrudes obliquely from the surface of the base 2, or extends from the surface of the base 2 in a direction perpendicular to the base 2 while bending at its tip and having a recessed portion between the protruding tip and the base 2. The cross-sectional structure of the overhang portion is not particularly limited, but is exemplified in (A) and (B) of FIG. 2. (A) of FIG. 2 is a schematic diagram showing an overhang portion 8 having a recessed portion 9 below the base 2 side of the protruding tip, and (B) of FIG. 2 is a schematic diagram showing a plurality (two) of overhang portions 8 on one convex portion. The size of the overhang portion 8 (height from the surface of the base 2, width from the protruding tip to the root of the recessed portion 9, etc.) is not particularly limited. The protruding tip can be needle-shaped, tapered plate-shaped, etc.
[0016] The number of overhangs on the surface of the base 2 is not particularly limited, but from the viewpoint of adhesion between the intermediate layer 4 and the base 2, it is preferably 10 to 10,000 per mm. 2 , more preferably 100 to 10,000 pieces / 1 mm 2 It is.
[0017] The overhang portion 8 is preferably formed by subjecting the surface of the article containing metallic aluminum or an aluminum alloy to an acid treatment, an electric discharge treatment, a shot blasting treatment, or an electrolytic etching treatment. The acid treatment, the electric discharge treatment, the shot blasting treatment, and the electrolytic etching treatment will be described later.
[0018] The intermediate layer 4 is made of at least one of an aggregate of wood chips impregnated with resin and a wooden board impregnated with resin. The resin contained in the intermediate layer 4 is not particularly limited as long as it has adhesive properties to the article, but is preferably derived from at least one of a thermosetting resin and a thermoplastic resin. Therefore, the resin contained in the intermediate layer 4 is usually at least one of a cured resin and a thermoplastic resin.
[0019] Examples of the thermosetting resin include melamine resin, phenol resin, urea resin, urethane resin, unsaturated polyester, diallyl phthalate, silicon resin, vinyl ester resin, polyimide resin, etc. Among these, from the viewpoint of adhesiveness, melamine resin, phenol resin, urea resin, and urethane resin are preferred. Examples of the thermoplastic resin include acrylic resin, olefin resin, styrene resin, polyester, polyamide resin, urethane resin, polyvinyl acetate, polyvinyl chloride, polyvinylidene chloride, polytetrafluoroethylene, polyacetal, polycarbonate, polyphenylene ether, polyphenylene sulfide, polysulfone, polyethersulfone, polyarylate, polyetheretherketone, polyimide, polyamideimide, etc. Among these, acrylic resin, styrene resin, and urethane resin are preferred from the viewpoint of adhesion.
[0020] The wood chips or wood boards contained in the intermediate layer 4 are derived from plants having cell walls, such as wood (conifers such as cedar, cypress, and pine; broad-leaved trees such as poplar, beech, oak, and birch), bamboo, flax (jute, kenaf, flax, hemp, ramie, sisal, and the like), and herbaceous plants, and may be the plant itself (sawn board, veneer, wood chips, powder, fiber, and the like), waste materials thereof, or chemically processed products thereof. The intermediate layer 4 may contain wood chips or wood boards of multiple tree species. In the present invention, veneer, veneer, wood chips, powder, and fiber are preferred from the viewpoint of resin impregnation. In addition, in the intermediate layer 4, it is preferred that a part of the resin is contained in the cell walls of the wood chips or wood boards.
[0021] There are no particular limitations on the shape and size of the wood pieces contained in the intermediate layer 4. The wood pieces may be either shaped or irregular, and the major axis thereof is preferably 0.05 to 10 mm, more preferably 0.05 to 5 mm. There is also no particular limitation on the shape and size of the wooden board included in the intermediate layer 4. The thickness of the wooden board is preferably 0.01 to 20 mm, and more preferably 0.05 to 5 mm.
[0022] The content ratios (mass ratios) of the wood chips and resin contained in the intermediate layer 4, when the total of both is taken as 100% by mass, are preferably 5 to 95% by mass and 5 to 95% by mass, more preferably 10 to 90% by mass and 10 to 90% by mass, and even more preferably 20 to 80% by mass and 20 to 80% by mass. The content ratios (mass ratios) of the wood boards and resin contained in the intermediate layer 4, when the total of both is taken as 100% by mass, are preferably 5 to 95% by mass and 5 to 95% by mass, more preferably 10 to 90% by mass and 10 to 90% by mass, and even more preferably 20 to 80% by mass and 20 to 80% by mass. When the content ratio of the wood chips or wood boards and the resin is within the above range, the adhesion between the intermediate layer 4 and the base 2 or the decorative layer 6 is excellent. Since the composite of the present invention has an overhang portion 8 on the surface of the base 2, the preferable configuration of the intermediate layer 4 as described above makes the structural stability of the composite particularly excellent.
[0023] The thickness of the intermediate layer 4 is appropriately selected depending on the type, application, etc. of the composite of the present invention, but is usually 0.01 to 20 mm, preferably 0.05 to 5 mm. From the viewpoint of adhesion between the intermediate layer 4 and the base 2 or the design layer 6, the resin is preferably contained throughout the intermediate layer 4, but depending on the shape, thickness, etc. of the intermediate layer 4, the resin may be contained only on the interface side between the base 2 and the design layer 6.
[0024] The design layer 6 is provided to impart design to the composite of the present invention. The design layer 6 may be either a single-layer type or a multi-layer type. The material constituting the design layer 6 is not particularly limited, and may be a thin wood body, i.e., a thin wood body obtained by processing wood, a resin film, paper, a wooden board, etc., and in any case, good adhesion with the intermediate layer 4 is exhibited. In the present invention, the design layer 6 preferably includes a thin wood body, and in this case, the outermost surface of the design layer 6 may be provided with a transparent protective film layer, a coating layer, etc.
[0025] The composite of the present invention can be manufactured using an aluminum-containing substrate having an overhang for the base 2, at least one of wood chips (crushed wood, etc.) and wood boards for the intermediate layer 4, a resin component (a thermoplastic resin precursor or a thermosetting resin) to be impregnated into the wood chips and wood boards, and a decorative material for the decorative layer 6.
[0026] Next, a method for producing the composite of the present invention will be described. One embodiment of the method for producing a composite of the present invention (hereinafter referred to as the "first production method") includes a step of subjecting a substrate containing metallic aluminum or an aluminum alloy (hereinafter referred to as the "aluminum substrate") to an acid treatment, an electric discharge machining treatment, a shot blasting treatment, or an electrolytic etching treatment to form a plurality of overhang portions on the surface of the aluminum substrate to produce an aluminum-containing roughened substrate (hereinafter referred to as the "aluminum-containing roughened substrate production step"); and a step of impregnating wood with a resin component containing at least one selected from a thermoplastic resin precursor (hereinafter also referred to as the "precursor composition") and a thermosetting resin. The method includes, in sequence, a step of crushing resin-component-impregnated wood to prepare resin-component-containing crushed wood material (hereinafter referred to as the "resin-component-containing crushed wood material preparation step"); a step of placing the resin-component-containing crushed wood material on the surface of the aluminum-containing roughened base material having the overhanging portion to prepare a first load (hereinafter referred to as the "first load preparation step"); a step of placing a decorative material on the resin-component-containing crushed wood material layer in the first load to prepare a second load (hereinafter referred to as the "second load preparation step"); and a step of subjecting the second load to hot pressing (hereinafter referred to as the "first hot pressing step").
[0027] In addition, another aspect of the composite manufacturing method of the present invention (hereinafter referred to as the "second manufacturing method") sequentially comprises the same aluminum-containing roughened substrate preparation step as in the first manufacturing method, a step of preparing a resin component-impregnated wooden board by impregnating a wooden board with a resin component containing at least one selected from a precursor of a thermoplastic resin (precursor composition) and a thermosetting resin (hereinafter referred to as the "resin component-impregnated wooden board preparation step"), a step of placing the resin component-impregnated wooden board on the surface having an overhang portion of the aluminum-containing roughened substrate to prepare a third load (hereinafter referred to as the "third load preparation step"), a step of placing a decorative material on the resin component-impregnated wooden board in the third load to prepare a fourth load (hereinafter referred to as the "fourth load preparation step"), and a step of subjecting the fourth load to hot pressing (hereinafter referred to as the "second hot pressing step").
[0028] In the present invention, the aluminum-containing roughened substrate preparation step according to the first and second production methods is a step of subjecting an aluminum substrate to an acid treatment, an electric discharge treatment, a shot blasting treatment, or an electrolytic etching treatment to form a plurality of overhang portions 8 on the surface of the aluminum substrate, thereby preparing an aluminum-containing roughened substrate 10 (see FIG. 3 ).
[0029] An example of an acid treatment method for an aluminum substrate is a method of contacting an aqueous acid solution with the aluminum substrate. The aqueous acid solution is not particularly limited, and may be one that comprises at least one of an inorganic acid and an organic acid, and water. Examples of the inorganic acid include hydrochloric acid, sulfuric acid, nitric acid, hydrofluoric acid, and phosphoric acid. Examples of the organic acid include acetic acid and citric acid. From the viewpoint of the formability of an overhang portion, the pH of the aqueous acid solution is preferably 6 or less, and more preferably 3 or less. The contact time between such an aqueous acid solution and the aluminum substrate is, for example, preferably 1 to 10 minutes, and more preferably 3 to 10 minutes, when an aqueous acid solution at 25°C is used.
[0030] An example of a method for electric discharge machining of an aluminum substrate is a method of applying a voltage between an aluminum substrate and an electrode in an insulating machining liquid. The insulating machining liquid is not particularly limited, and liquids having insulating properties such as water and oil can be used. The electrode material is also not particularly limited, and can be conductive, and examples of the electrode material include copper, brass, tungsten, and graphite. Furthermore, the size and shape of the electrode are not limited, and wires, rods, tubes, bulks, and the like can be used.
[0031] An example of a method for shot blasting an aluminum substrate is a method of colliding particles called shot media with the surface of the aluminum substrate. Examples of the shot media include iron particles, stainless steel particles, aluminum particles, zinc particles, copper particles, glass beads, ceramic particles (alumina particles, silicon carbide particles, silicon nitride particles, zirconia particles, etc.), and resin particles. The particle size of the shot media is not particularly limited, but is usually 10 to 4000 μm, and preferably 100 to 2000 μm.
[0032] In the aluminum-containing roughened substrate preparation step, when acid treatment, electric discharge machining treatment, shot blasting treatment, or electrolytic etching treatment is performed, a plurality of overhanging portions are formed, while an aluminum oxide layer may be formed on the surface of the obtained aluminum-containing roughened substrate, or the overhanging portions may be made of aluminum oxide. In the present invention, even if the state of aluminum on the surface of the aluminum-containing roughened substrate after each of the above surface treatments is not the same as before the surface treatment, the substrate can be directly advanced to the first load preparation step (in the case of the first production method) or the third load preparation step (in the case of the second production method).
[0033] The resin component-containing crushed wood product production process in the first manufacturing method is a process of crushing resin component-impregnated wood, in which wood is impregnated with a resin component containing at least one type selected from a precursor composition and a thermosetting resin, to produce resin component-containing crushed wood product. When the resin component is a precursor (precursor composition) of a thermoplastic resin, the resin component-impregnated wood is wood impregnated with the precursor composition, and this can be crushed as is to produce resin component-containing crushed wood, which is precursor composition-containing crushed wood. Furthermore, when the resin component is a thermosetting resin, the resin component-impregnated wood is thermosetting resin-impregnated wood, and the thermosetting resin can be crushed while still uncured to produce thermosetting resin-containing wood crushed material, which is a resin component-containing wood crushed material.
[0034] The wood used in the first manufacturing method may be either a coniferous or broadleaf tree, and the wood used in the resin component-containing crushed wood production step may be either a shaped or an unshaped one. The wood may be from a plurality of tree species. In the first load production step, a plurality of resin component-containing crushed wood pieces are usually used, and it is preferable that they are not irregular in shape or have a small variation in size. In order to obtain such resin component-containing crushed wood pieces, it is preferable that the wood used in the resin component-containing crushed wood production step is a shaped one. In this case, for example, the wooden board is made of a coniferous or broadleaf tree, and can be obtained by cutting or machining lumber. The shape and size of the wooden board are not particularly limited, but from the viewpoint of the impregnation of the precursor composition or the thermosetting resin into the wooden board, the thickness of the wooden board is preferably 0.5 to 10 mm, more preferably 1 to 5 mm. The coniferous and broadleaf trees exemplified above can be used.
[0035] The resin component-impregnated wood is obtained by impregnating wood with at least one material selected from a precursor composition and a thermosetting resin.
[0036] For example, thermosetting resin-impregnated wood may be wood impregnated with only a thermosetting resin, or may be wood impregnated with a thermosetting resin and a curing agent, or may be wood impregnated with a thermosetting resin and a thermoplastic resin, or may be wood impregnated with a thermosetting resin and a precursor composition.
[0037] The thermosetting resin is preferably a melamine resin, a phenol resin, a urea resin or a urethane resin, and more preferably a melamine resin. The content of the thermosetting resin in the thermosetting resin-impregnated wood, or the total content of the thermosetting resin and the curing agent, is preferably 5 to 1,900 parts by mass, and more preferably 11 to 900 parts by mass, relative to 100 parts by mass of the wood.
[0038] In the present invention, the combined use of a thermosetting resin and a precursor (precursor composition) of a thermoplastic resin is a preferred method for forming an intermediate layer that firmly bonds the aluminum-containing roughened substrate and the decorative material. The precursor (precursor composition) of the thermoplastic resin may be a precursor composition of a urethane resin, which is a thermoplastic resin. This precursor composition is preferably a composition containing a blocked isocyanate compound and polyethylene glycol (hereinafter referred to as a "urethane resin forming composition").
[0039] The blocked isocyanate compound is preferably a compound formed from an isocyanate compound and a blocking agent that protects an isocyanate group contained in the isocyanate compound, and is inactivated by a group derived from the blocking agent. In the present invention, the blocked isocyanate compound is more preferably a compound that is deblocked by heating at a temperature of 40°C to 200°C, that is, the group derived from the blocking agent is dissociated to produce the isocyanate compound. In addition, a particularly preferred blocked isocyanate compound is a compound that forms a thermoplastic polyurethane by reacting the blocked isocyanate compound after deblocking with the ethylene glycol.
[0040] The isocyanate compound is not particularly limited as long as it has an isocyanate group. The number of isocyanate groups contained is preferably 1 to 5, more preferably 1 to 2, and particularly preferably 1. The isocyanate compound may have other functional groups, such as a (meth)acryloyloxy group, in addition to the isocyanate group.
[0041] Examples of the blocking agent include oximes such as formamidoxime, acetaldoxime, acetoxime, methyl ethyl ketoxime, diacetyl monoxime, benzophenone oxime, and cyclohexanone oxime; active methylenes such as dimethyl malonate, diethyl malonate, ethyl acetoacetate, methyl acetoacetate, and acetylacetone; lactams such as ε-caprolactam, δ-valerolactam, γ-butyrolactam, and β-propiolactam; phenols such as phenol, cresol, resorcinol, and xylenol; and alcohols such as methanol, ethanol, n-propyl alcohol, isopropyl alcohol, n-butyl alcohol, isobutyl alcohol, sec-butyl alcohol, tert-butyl alcohol, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monoethyl ether, propylene glycol monomethyl ether, and benzyl alcohol.
[0042] The blocked isocyanate compound is particularly preferably a compound having one -N(H)CO as a structure before being deblocked by heating, and a group derived from a blocking agent being bonded to the C atom of this -N(H)CO. For example, when the blocking agent is methyl ethyl ketoxime, the compound is one in which -ON=C(CH3)C2H5, which is the H atom removed from methyl ethyl ketoxime, is bonded to the C atom of -N(H)CO. As described above, the blocked isocyanate compound which is deblocked to produce the isocyanate compound having another functional group, such as a (meth)acryloyloxy group in a preferred embodiment, preferably has a (meth)acryloyloxy group. By using such a blocked isocyanate compound having a (meth)acryloyloxy group, it is possible to obtain thermosetting resin-impregnated wood in which thermoplastic polyurethane and thermosetting resin are contained in the cell walls of the wood.
[0043] The blocked isocyanate compound is particularly preferably 2-[0-(1'-methylpropylideneamino)carboxyamino]ethyl methacrylate, since it is liquid at room temperature, easily penetrates into the cell walls of wood, and can generate an isocyanate compound at temperatures of 200°C or less, which does not decompose wood.
[0044] The polyethylene glycol is preferably a compound represented by the following general formula (1). HO-(CH2-CH2-O) n -H (1) In the above general formula (1), n is preferably 1 to 12,000, more preferably 4 to 500, and even more preferably 10 to 450, from the viewpoint of permeability into wood cell walls.
[0045] In the urethane resin forming composition, the content ratio of the blocked isocyanate compound and the polyethylene glycol can be appropriately set depending on the number of isocyanate groups contained in the isocyanate compound generated from the blocked isocyanate compound. In the present invention, when the total of the blocked isocyanate compound and the polyethylene glycol is 100 mass%, the content ratios thereof are preferably 5 to 95 mass% and 5 to 95 mass%, more preferably 20 to 80 mass% and 20 to 80 mass%, and further preferably 35 to 65 mass% and 35 to 65 mass%, respectively.
[0046] The urethane resin forming composition may consist of only the blocked isocyanate compound and the polyethylene glycol, or may further contain other materials such as liquid media such as water and organic solvents, antioxidants, heat stabilizers, plasticizers, etc.
[0047] In the present invention, when the urethane resin forming composition, which is the precursor composition, is used in combination with a thermosetting resin, the total amount of the blocked isocyanate compound and the polyethylene glycol used is preferably 5 to 2,000 parts by mass, and more preferably 20 to 1,000 parts by mass, relative to 100 parts by mass of the amount of the thermosetting resin used, or the total amount of the thermosetting resin and the curing agent used.
[0048] The precursor composition-impregnated wood is preferably prepared by impregnating a wooden board or piece with the urethane resin-forming composition as the precursor composition.
[0049] The method for producing the resin-impregnated wood is not particularly limited, and may be a method in which the wood is brought into contact with a precursor composition or a thermosetting resin. The contact conditions are appropriately set depending on the types of the precursor composition and the thermosetting resin. The resin-impregnated wood may have a coating containing the precursor composition or the thermosetting resin on its surface.
[0050] In the resin component-containing crushed wood product preparation step according to the first manufacturing method, the method for crushing the resin component-impregnated wood is not particularly limited as long as the precursor composition or thermosetting resin contained therein is not denatured, and a conventionally known crusher or the like can be used. The shape and size of the resin component-containing crushed wood product obtained are also not particularly limited, and it is not necessarily required to have a uniform shape and size, but from the viewpoint of the workability of the first load preparation step and the adhesion to the aluminum-containing roughened substrate and the design material, the major axis is preferably 0.05 to 10 mm, more preferably 0.1 to 5 mm.
[0051] The first load preparation step in the first manufacturing method is a step of placing resin component-containing crushed wood (precursor composition-containing crushed wood, or uncured thermosetting resin-containing crushed wood) on the surface of the aluminum-containing roughened base material having an overhanging portion to prepare the first load. The method of placing the resin component-containing crushed wood and the amount of the resin component-containing crushed wood are appropriately selected and not particularly limited depending on the adhesion area of the aluminum-containing roughened base material and the design material. In general, it is preferable to place multiple resin component-containing crushed wood on the entire surface of a predetermined surface of the aluminum-containing roughened base material without gaps, but as long as the first hot pressing step suppresses void formation and a high-density intermediate layer made of a continuous phase is obtained, multiple resin component-containing crushed wood may be placed, for example, at equal intervals, so that a part of the surface of the aluminum-containing roughened base material is exposed.
[0052] The second load preparation step in the first manufacturing method is a step of placing a decorative material on the resin component-containing crushed wood layer in the first load to prepare the second load. The decorative material can be a thin wood body, a thin wood body impregnated in whole or in part with a precursor composition or a thermosetting resin, a resin film, paper, a wooden board, etc. The thickness of the decorative material is not particularly limited.
[0053] The first hot pressing step of the first manufacturing method is a step of subjecting a second load, which is a resin component-containing crushed wood material and a design material placed in sequence on an aluminum-containing roughened base material, to hot pressing. The pressure direction is usually the loading direction. The press load and heating temperature are appropriately selected depending on the type of precursor composition or thermosetting resin contained in the resin component-containing crushed wood material, and are not particularly limited. In the first hot pressing step, the heating and pressing of the second load may be performed simultaneously, or the pressing of the second load may be delayed, and heating may be performed first, and then pressing may be performed.
[0054] When using thermosetting resin-containing wood crushed material containing the above-mentioned urethane resin forming composition as the resin component-containing wood crushed material, the blocked isocyanate compound is efficiently deblocked to produce an isocyanate compound, which reacts with polyethylene glycol to smoothly form polyurethane, so the heating temperature of the second load is preferably 80°C or higher, more preferably 100°C or higher.
[0055] The first hot pressing process makes it possible to efficiently produce a composite with excellent structural stability consisting of an integrated body in which an aluminum-containing base and a decorative layer are joined via an intermediate layer made of a collection of resin-impregnated wood pieces.
[0056] Next, the second manufacturing method will be described. In the second manufacturing method, a resin-impregnated wooden board is manufactured (resin-impregnated wooden board manufacturing process), and then, a third load is manufactured by placing the resin-impregnated wooden board on the surface having an overhang portion of the aluminum-containing roughened base material obtained in the same aluminum-containing roughened base material manufacturing process as in the first manufacturing method (third load manufacturing process), and then, a decorative material is placed on the resin-impregnated wooden board in this third load to manufacture a fourth load (fourth load manufacturing process), and then, this fourth load is subjected to a hot press (second hot press process). In the first manufacturing method, a plurality of resin-containing wood crushed pieces are placed between the aluminum-containing roughened base material and the decorative material when manufacturing a composite, but in the second manufacturing method, at least one resin-impregnated wooden board is placed between the aluminum-containing roughened base material and the decorative material to manufacture a composite.
[0057] The resin component-impregnated wooden board preparation process in the second manufacturing method is a process for preparing a resin component-impregnated wooden board (a wooden board containing a precursor composition, or a wooden board containing an uncured thermosetting resin) by impregnating a wooden board with a resin component containing at least one selected from a precursor composition and a thermosetting resin. The wooden board may be made of a softwood or hardwood, and the resin-impregnated wooden board may be a resin-impregnated lumber obtained by using a wooden board as the lumber in the first manufacturing method. Furthermore, the resin component may be the same as that in the first production method.
[0058] The method for producing the resin-impregnated wooden board is not particularly limited, and may be a method in which a precursor composition or a thermosetting resin is brought into contact with a wooden board having a thickness of preferably 0.01 to 20 mm, more preferably 0.05 to 5 mm. The contact conditions are appropriately set depending on the thickness of the wooden board, the type of the precursor composition and the thermosetting resin, etc. The resin-impregnated wooden board obtained by the resin-impregnated wooden board production step may have a coating containing the precursor composition or the thermosetting resin on its surface.
[0059] The third load preparation step in the second manufacturing method is a step of placing a resin component-impregnated wooden board (a wooden board containing a precursor composition or a wooden board containing an uncured thermosetting resin) on the surface of the aluminum-containing roughened substrate having an overhanging portion to prepare a third load. The external shape of the resin component-impregnated wooden board is usually almost the same as that of the decorative material, and is almost the same as the shape drawn by connecting the extreme ends of the overhanging portions formed on the aluminum-containing roughened substrate. The amount of resin component-impregnated wooden board placed on the aluminum-containing roughened substrate (amount used) is not particularly limited.
[0060] The second load preparing step and the first hot-pressing step in the first manufacturing method can be directly applied to the fourth load preparing step and the second hot-pressing step in the second manufacturing method, respectively. The second hot pressing process makes it possible to efficiently produce a composite with excellent structural stability consisting of an integrated body in which an aluminum-containing base and a decorative layer are joined via an intermediate layer made of a resin-impregnated wooden board.
[0061] The composite of the present invention is suitable for use as building materials and construction components, furniture and furnishings, vehicle components, home appliance parts, daily necessities, etc.
[0062] When the third load in the second manufacturing method is subjected to a hot press in the loading direction, a bonded body of the resin-impregnated wood board and the aluminum-containing roughened base material can be obtained. If a good wood grain pattern or the like is observed on the surface of the resin-impregnated wood board on the side not bonded to the aluminum-containing roughened base material, this bonded body can also be suitably used for the above-mentioned composite. EXAMPLES
[0063] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0064] 1. Preparation of Aluminum-containing Roughened Substrates A roughened metal aluminum substrate was prepared by applying the following methods 1 (acid treatment), 2 (electric discharge machining), 3 (shot blasting), and 4 (sanding) to a flat plate (thickness: 1.6 mm) made of metal aluminum (material: A1050) or aluminum alloy (material: AC4CH, ADC12).
[0065] (Method 1) A flat plate of a metal aluminum substrate was immersed in hydrochloric acid (pH 0.5) at 25° C. for 10 minutes to carry out an acid treatment. (Method 2) Using a Fanuc wire electric discharge machine "α-C400iA," tap water was used as the machining fluid and a brass wire (φ0.3 mm) was used as the electrode to perform electric discharge machining on the surface of the metal aluminum base material. (Method 3) Using a circulating sandblaster "Cycle Blaster Jr." manufactured by Daiei Dental Industry Co., Ltd., glass beads with a diameter of 600 to 850 μm were sprayed onto the surface of the metal aluminum base material at an air pressure of 0.40 MPa for 10 seconds to perform a shot blasting treatment. (Method 4) Using SiC waterproof abrasive paper #120 (abrasive grain size 125 μm or less), the surface of the metal aluminum base material was sanded under dry conditions until the metallic luster was lost.
[0066] Cross sections of each of the aluminum-containing roughened substrates obtained by methods 1, 2, 3, and 4 were photographed using a digital microscope "VHX-5000" manufactured by Keyence Corporation so as to include the outermost surface, and are shown in FIGS. Fig. 4 is a cross-sectional image of the metal aluminum sheet before surface treatment, Figs. 5, 6 and 7 are cross-sectional images of the metal aluminum sheet, the aluminum alloy sheet (AC4CH) and the aluminum alloy sheet (ADC12) respectively after acid treatment, Fig. 8 is a cross-sectional image of the metal aluminum sheet after electric discharge machining, Fig. 9 is a cross-sectional image of the aluminum alloy sheet (ADC12) after shot blasting treatment, and Fig. 10 is a cross-sectional image of the metal aluminum sheet after sanding. As is clear from Figures 5 to 10, according to Methods 1, 2, and 3, an overhang portion is formed on the surface of the metal aluminum base material, while according to Method 4, an overhang portion is not formed on the surface of the metal aluminum base material.
[0067] 2. Preparation of thermosetting resin-containing wood crushed material Thermosetting resin-containing crushed wood was obtained by producing a thermosetting resin-impregnated wooden board and then crushing it while it was still uncured, or by contacting the crushed wood with a thermosetting resin.
[0068] Preparation Example 1-1 (Preparation of melamine resin-containing wood crushed material) First, several plate-shaped samples (size: 80 mm (in the direction of the grain) x approximately 80 mm (in the direction perpendicular to the grain)) were made from cypress veneer (thickness 1 mm) and dried in air at 105°C for more than one hour. On the other hand, as a thermosetting resin, a melamine / formaldehyde resin “Amidia M-3(60)” (product name) manufactured by DIC Corporation was diluted with water to obtain a melamine / formaldehyde resin aqueous solution having a solid content of 50 mass% (hereinafter referred to as “melamine resin aqueous solution (1)”). Next, the above-mentioned dried plate-shaped sample was immersed in a container containing an aqueous melamine resin solution (1) at about 20°C, and in that state, the pressure was reduced (0.01 MPa, 1 hour) at room temperature (about 20°C), and then the pressure was increased (0.8 MPa, about 18 hours). The plate-shaped sample impregnated with the aqueous melamine resin solution (1) was removed from the container, placed on a wire rack, and air-dried at room temperature (about 20°C) for 2 days. Next, the plate-shaped sample was dried at 35°C for about 3 days using a blower dryer, and further dried at 35°C for 2 days or more using a vacuum dryer, to obtain a melamine resin-containing plate-shaped sample W1 (weight increase rate: 118% by mass) as a thermosetting resin-impregnated wooden board. Thereafter, the melamine resin-containing plate-shaped sample W1 was crushed for about 30 seconds using a crusher "Wonder Crush / Mill WDL-1" (trade name) manufactured by Osaka Chemical Co., Ltd., to obtain a melamine resin-containing wood crushed material C1 as a thermosetting resin-containing wood crushed material. The melamine resin-containing wood crushed material C1 was then sieved and classified, and three types of melamine resin-containing wood crushed material C1-1 (150 μm_pass) that passed through a mesh size of 150 μm, melamine resin-containing wood crushed material C1-2 (150-300 μm) that passed through a mesh size of 300 μm but did not pass through a mesh size of 150 μm, and melamine resin-containing wood crushed material C1-3 (300 μm_on) that did not pass through a mesh size of 300 μm were collected. All of these melamine resin-containing wood crushed materials contained wood cell fibers and had an elongated shape (average aspect ratio of 5 or more).
[0069] Preparation Example 1-2 (Preparation of melamine resin-containing wood crushed material) First, peeled cypress veneer (3 mm thick) was crushed for about 30 seconds using the above-mentioned crusher to obtain wood crushed material (shape: rod-like, size: diameter of about 500 mm or less). Next, the above-mentioned crushed wood was immersed in a container containing an aqueous melamine resin solution (1) at about 20°C, and in that state, the pressure was reduced (0.01 MPa, 1 hour) at room temperature (about 20°C), and then pressurized (0.8 MPa, about 18 hours). The crushed wood impregnated with the aqueous melamine resin solution (1) was removed from the container, placed on a wire rack, and air-dried at room temperature (about 20°C) for 2 days. Next, the crushed wood was dried at 35°C for about 3 days using a blower dryer, and further dried at 35°C for more than 2 days using a vacuum dryer, to obtain melamine resin-containing crushed wood C2 (weight increase rate: 91% by mass) as thermosetting resin-impregnated wood.
[0070] 3. Preparation of wood chips containing precursor composition The crushed wood was contacted with a precursor composition of a thermoplastic polyurethane resin to obtain the crushed wood containing the precursor composition.
[0071] Preparation Example 2-1 (Preparation of Crushed Wood Containing Polyurethane Precursor Composition) First, peeled cypress veneer (3 mm thick) was crushed for about 30 seconds using the above-mentioned crusher to obtain wood crushed material (shape: rod-like, size: diameter of about 500 mm or less). On the other hand, as a precursor composition of polyurethane resin, a blocked isocyanate compound, 2-[0-(1'-methylpropylideneamino)carboxyamino]ethyl methacrylate "Karends MOI-BM" (trade name) manufactured by Showa Denko K.K. and polyethylene glycol "PEG-1540" (trade name, molecular weight: 1540) manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., diluted with a solvent was used. This precursor composition was prepared by dissolving polyethylene glycol melted at 60°C in water to prepare an aqueous polyethylene glycol solution, cooling this aqueous polyethylene glycol solution to room temperature, mixing it with an ethanol solution obtained by dissolving the blocked isocyanate compound in ethanol, and adding water as necessary, and it was a liquid composition in which the ratio of polyethylene glycol:blocked isocyanate compound was 1:1 (mass ratio) and the solid content concentration was 50 mass%, 30 mass%, or 10 mass%. Next, instead of the melamine resin aqueous solution (1), the above-mentioned precursor compositions having a solid content concentration of 50 mass%, 30 mass%, or 10 mass% were used, and the same operation as in Preparation Example 1-2 was performed to obtain three types of wood crushed materials containing a precursor composition of a thermoplastic polyurethane resin. The one obtained using the precursor composition having a solid content concentration of 50 mass% was called precursor composition-containing wood crushed material C3 (weight increase rate: 81 mass%), the one obtained using the precursor composition having a solid content concentration of 30 mass% was called precursor composition-containing wood crushed material C4 (weight increase rate: 41 mass%), and the one obtained using the precursor composition having a solid content concentration of 10 mass% was called precursor composition-containing wood crushed material C5 (weight increase rate: 13 mass%).
[0072] 4. Preparation of Thermosetting Resin-impregnated Wood Boards The melamine resin aqueous solution (1), which is a melamine / formaldehyde resin aqueous solution having a solid content concentration of 50 mass% used in Preparation Example 1-1, the melamine resin aqueous solution (2), which is a melamine / formaldehyde resin aqueous solution having a lower solid content concentration of 30 mass%, and the phenol / formaldehyde resin aqueous solution were each applied to a cypress board to produce a thermosetting resin-impregnated wooden board.
[0073] Preparation Example 3-1 First, several plate-shaped samples (size: approximately 100 mm (in the direction of the grain) × approximately 200 mm (in the direction perpendicular to the grain)) were made from peeled Hinoki veneer (thickness 3 mm) and dried in air at 105°C for more than 1 hour. Next, the dried plate-shaped sample was immersed in a container containing the melamine resin aqueous solution (1) or (2) at about 20°C, and in that state, the pressure was reduced (0.01 MPa, 1 hour) at room temperature (about 20°C), and then pressurized (0.8 MPa, about 18 hours). The plate-shaped sample impregnated with the melamine resin aqueous solution was then removed from the container, placed on a wire rack, and air-dried at room temperature (about 20°C) for 2 days. Next, the plate-shaped sample was dried at 35°C for about 3 days using a blower dryer, and further dried at 35°C for 2 days or more using a reduced-pressure dryer. Then, the sample was cut to obtain a thermosetting resin-impregnated wooden board having a size of 10 mm (in the fiber direction) x 10 mm (in the direction perpendicular to the fiber) x about 3 mm (thickness). The melamine resin-impregnated wooden board W2 (weight increase rate: 110% by mass) was obtained using melamine resin aqueous solution (1), which was a melamine / formaldehyde-based resin aqueous solution with a solid content concentration of 50% by mass, and the melamine resin-impregnated wooden board W3 (weight increase rate: 69% by mass) was obtained using melamine resin aqueous solution (2), which was a melamine / formaldehyde-based resin aqueous solution with a solid content concentration of 30% by mass.
[0074] Preparation Example 3-2 The same operations as in Preparation Example 3-1 were carried out to obtain a phenolic resin-impregnated wooden board W4 (weight increase rate: 127% by mass), except that an aqueous solution obtained by diluting AIKA Electroresin PX-341 (product name) manufactured by AIKA Kogyo Co., Ltd. with water (solid content concentration: 50% by mass, hereinafter referred to as "phenolic resin aqueous solution") was used instead of the melamine resin aqueous solution.
[0075] 5. Preparation of Precursor Composition-impregnated Wood Boards The polyurethane resin precursor composition used in Preparation Example 2-1 was used to obtain a wooden board impregnated with the precursor composition.
[0076] Preparation Example 4-1 The polyurethane resin precursor composition used in Preparation Example 2-1 was used and cut in the same manner as in Preparation Example 3-1 to obtain a precursor composition-impregnated wooden board W5 (weight increase rate: 64% by mass).
[0077] 6. Fabrication of design materials The design materials used in the manufacture of the composites or laminates (for reference purposes) are shown below.
[0078] Preparation Example 5-1 (Preparation of wood board containing melamine resin-added polyurethane precursor) First, several plate-shaped samples (size: 200 mm (in the direction of the grain) × approximately 300 mm (in the direction perpendicular to the grain)) were made from cypress veneer (thickness 4 mm) and dried in air at 105°C for more than 1 hour. On the other hand, as the precursor composition to be impregnated into the plate-shaped sample, a blocked isocyanate compound, 2-[0-(1'-methylpropylideneamino)carboxyamino]ethyl methacrylate "Karends MOI-BM" (trade name) manufactured by Showa Denko K.K., polyethylene glycol "PEG-1540" (trade name, molecular weight: 1540) manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., and melamine / formaldehyde resin "Amidea M-3(60)" (trade name) manufactured by DIC Corporation, diluted with a solvent, were used. This precursor composition was prepared by dissolving polyethylene glycol melted at 60°C in water to prepare an aqueous polyethylene glycol solution, cooling this aqueous polyethylene glycol solution to room temperature, adding the melamine / formaldehyde resin to prepare a mixed solution, mixing this mixed solution with an ethanol solution obtained by dissolving the blocked isocyanate compound in ethanol, and adding water as necessary. By this preparation method, a melamine resin-added polyurethane precursor-containing liquid was obtained that contained 35% by mass of ethanol, had a polyethylene glycol 1540:blocked isocyanate compound:melamine / formaldehyde resin=1:1:1 (mass ratio), and had a solids concentration of 20% by mass. Thereafter, a plate-shaped sample was impregnated with the melamine resin-added polyurethane precursor-containing liquid in the same manner as in Preparation Example 1-1, except that this melamine resin-added polyurethane precursor-containing liquid was used instead of the melamine resin aqueous solution, to obtain a melamine resin-added polyurethane precursor-containing wooden board (mass increase rate: 43 mass%, hereinafter referred to as "design material DD1").
[0079] Example 5-2 Hinoki cypress veneer (thickness 4 mm) was cut and processed to produce a plate-shaped sample (size: 10 mm (in the direction of the grain) x 10 mm (orthogonal to the direction of the grain)) with wood grain on the surface, which was used as a decorative material (hereinafter referred to as "decorative material DD2").
[0080] 7. Preparation and Evaluation of the Complex A composite having a multi-layer structure was produced using an aluminum-containing roughened substrate, resin-containing crushed wood or a resin-impregnated wood board, and a decorative material.
[0081] Example 1 A metal aluminum plate (size: 20 mm x 20 mm) having an overhang made of A1050 obtained by acid treatment based on the above method 1 was placed on a hot plate preheated to 170°C with its rough surface facing up and heated. Next, about 1 g of melamine resin-containing crushed wood C1 was evenly distributed on the rough surface of the metal aluminum plate, and further, a design material DD1 was placed on it and hot pressed (170°C, 2 kN (5 MPa), 5 minutes). After that, it was cooled to about 40°C to obtain a composite.
[0082] An external image of the obtained composite (with the design surface facing up) is shown in Figure 11. A cross-sectional image is shown in Figure 12. It can be seen from these figures that the resin precursor contained in the melamine resin-containing crushed wood material C1 is modified into a hardened resin by the heat press, forming an adhesive layer (intermediate layer) (4) that is dense enough to prevent voids from forming, and satisfactorily bonding the acid-treated surface of the metal aluminum plate (2) and the design material DD1 (6). Furthermore, as can be seen from Figure 11, the surface of the design layer (6) of the composite has good wood texture with no loss of wood grain.
[0083] FIG. 13 is an enlarged image of the bonding interface between the intermediate layer (4) of the obtained composite and the metal aluminum plate (2). From FIG. 13, it can be seen that the uneven parts on the surface of the metal aluminum plate, which are several tens of microns in size, are filled with wood cells (cell walls) and hardened melamine resin contained in the melamine resin-containing crushed wood material C1. It was also observed that the melamine resin oozed from the melamine resin-containing crushed wood material C1 into the inside of the fine overhang parts, which are even smaller and are several microns in size, and then became a hardened resin and filled the parts without any gaps. The present inventors believe that the hardened resin in the overhang parts and the engagement of the wood cells provide a strong bond and exhibit structural stability of the composite. The arrows (three places) shown in FIG. 13 are cell walls derived from the Japanese cypress that constitute the melamine resin-containing crushed wood material C1.
[0084] Example 2 A composite was obtained in the same manner as in Example 1 (not shown), except that a metal aluminum plate having an overhang made of A1050 and obtained by electrical discharge machining in the above-mentioned method 2 was used instead of the metal aluminum plate obtained by acid treatment based on the above-mentioned method 1. When this composite was visually observed, the appearance was as good as that of the composite obtained in Example 1.
[0085] Comparative Example 1 The same operation as in Example 1 was carried out, except that a metal aluminum plate made of A1050 that had not been surface-treated was used instead of the metal aluminum plate obtained by acid treatment based on the above-mentioned Method 1. However, no integrated product was obtained after hot pressing.
[0086] Comparative Example 2 The same operation as in Example 1 was carried out, except that a metal aluminum plate made of A1050 with a sanded surface was used instead of the metal aluminum plate obtained by acid treatment based on the above-mentioned Method 1. However, no integrated product was obtained after hot pressing.
[0087] Example 3 A metal aluminum plate (size: about 10 mm x about 10 mm) having an overhang made of A1050 obtained by acid treatment based on the above method 1 was placed on a hot plate preheated to 170 ° C. with its rough surface facing up and heated. Next, this metal aluminum plate was placed in a mold (inner dimensions: 10 mm x 10 mm) preheated to 170 ° C. with its rough surface facing up, and the above melamine resin-impregnated wood board W2 (size: 10 mm x 10 mm x about 3 mm) and the design material DD2 were placed on top of it in this order, and hot pressing (170 ° C., 0.5 kN (5 MPa), 5 minutes) was performed. After that, it was cooled to about 40 ° C. to obtain a composite. An external image of the obtained composite (the design side is the top surface) is shown in Figure 14. It can be seen that the acid-treated surface of the metal aluminum plate and the design material DD2 are well bonded via an adhesive layer (intermediate layer) containing melamine cured resin. Furthermore, the surface of the design layer of the composite retained the high quality texture of the wood, with the cypress grain of the design material DD2 intact.
[0088] 8. Manufacturing and Evaluation of Laminates (1) The use of decorative materials was omitted, and instead, crushed wood material containing resin components was used to form an adhesive layer (intermediate layer) on the surface of a metal aluminum base material to form a laminate, and an experiment was conducted to confirm whether the two could be bonded properly.
[0089] Reference example 1-1 An aluminum alloy plate (size: about 10 mm x about 10 mm) having an overhang made of AC4CH obtained by acid treatment based on the above method 1 was placed on a hot plate preheated to 170 ° C with its rough surface facing up and heated. Next, this aluminum alloy plate was placed in a mold (inner dimensions: 10 mm x 10 mm) preheated to 170 ° C with its rough surface facing up, and about 1 g of the above melamine resin-containing wood crushed material C2 was evenly distributed on it and hot pressed (170 ° C, 0.5 kN (5 MPa), 5 minutes). Then, it was cooled to about 40 ° C to obtain a laminate. When this laminate was visually observed, it was found that an aggregate of wood pieces containing melamine cured resin constituted a high-density layer and was well bonded to the rough surface of the aluminum alloy plate.
[0090] Reference example 1-2 A laminate was obtained in the same manner as in Reference Example 1-1, except that an aluminum alloy plate having an overhang made of ADC12 was used instead of an aluminum alloy plate made of AC4CH. In this laminate, too, an assembly of wood pieces containing melamine cured resin constituted a high-density layer and was well bonded to the rough surface of the aluminum alloy plate.
[0091] Reference example 1-3 A laminate was obtained in the same manner as in Reference Example 1-1, except that an aluminum alloy plate having an overhang made of ADC12 was used instead of an aluminum alloy plate made of AC4CH, and a precursor composition-containing crushed wood material C3 was used instead of a melamine resin-containing crushed wood material C2. When this laminate was visually observed, it was found that an aggregate of wood chips containing polyurethane resin constituted a high-density layer and was well bonded to the rough surface of the aluminum alloy plate.
[0092] Reference example 1-4 Except for using the aluminum alloy plate having an overhang made of ADC12 instead of the aluminum alloy plate made of AC4CH, and using the wood crushed material C4 containing precursor composition instead of the wood crushed material C2 containing melamine resin, obtain a laminate in the same manner as in Reference Example 1-1. In this laminate, too, the aggregate of wood chips containing polyurethane resin forms a high-density layer and is well bonded to the rough surface of the aluminum alloy plate.
[0093] Reference example 1-5 Except for using the aluminum alloy plate having an overhang made of ADC12 instead of the aluminum alloy plate made of AC4CH, and using the wood crushed material C5 containing precursor composition instead of the wood crushed material C2 containing melamine resin, obtain a laminate in the same manner as in Reference Example 1-1. In this laminate, too, the aggregate of wood chips containing polyurethane resin forms a high-density layer and is well bonded to the rough surface of the aluminum alloy plate.
[0094] 9. Manufacturing and evaluation of laminates (2) The use of decorative materials was omitted, and instead, a resin-impregnated wooden board was used to form an adhesive layer (intermediate layer) on the surface of the metal aluminum base material to create a laminate, and an experiment was conducted to confirm whether the two could be bonded properly.
[0095] Reference example 2-1 A metal aluminum plate (size: about 10 mm x about 10 mm) having an overhang made of A1050 obtained by acid treatment based on the above method 1 was placed on a hot plate heated to 170 ° C. with its rough surface facing up and heated. Next, this metal aluminum plate was placed in a mold (inner dimensions: 10 mm x 10 mm) heated to 170 ° C. with its rough surface facing up, and the melamine resin-impregnated wood board W2 obtained in Preparation Example 3-1 (size: 10 mm x 10 mm x about 3 mm) was placed on top of it and heated and pressed (170 ° C., 0.5 kN (5 MPa), 5 minutes). Then, it was cooled to about 40 ° C. to obtain a laminate. When this laminate was visually observed, it was found that the thin plate containing the melamine cured resin was well adhered to the rough surface of the metal aluminum plate.
[0096] Reference example 2-2 Except for using the aluminum alloy plate having an overhang made of AC4CH instead of the metal aluminum plate made of A1050, a laminate was obtained in the same manner as in Reference Example 2-1. In this laminate, the thin plate containing melamine cured resin was also well bonded to the rough surface of the aluminum alloy plate.
[0097] Reference example 2-3 Except for using the aluminum alloy plate having an overhang made of ADC12 instead of the metal aluminum plate made of A1050, obtain a laminate in the same manner as in Reference Example 2-1. In this laminate, the thin plate containing melamine cured resin is well bonded to the rough surface of the aluminum alloy plate.
[0098] Reference example 2-4 A laminate was obtained in the same manner as in Reference Example 2-1, except that the melamine resin-impregnated wooden board W3 (size: 10 mm x 10 mm x about 3 mm) obtained in Preparation Example 3-1 was used instead of the melamine resin-impregnated wooden board W2. In this laminate, the thin plate containing the melamine cured resin was also well bonded to the rough surface of the metal aluminum plate.
[0099] Reference example 2-5 A laminate was obtained in the same manner as in Reference Example 2-1, except that an aluminum alloy plate having an overhang made of AC4CH was used instead of the metal aluminum plate made of A1050, and a melamine resin-impregnated wooden board W3 (size: 10mm x 10mm x about 3mm) obtained in Preparation Example 3-1 was used instead of the melamine resin-impregnated wooden board W2. In this laminate, the thin plate containing melamine cured resin was well bonded to the rough surface of the aluminum alloy plate.
[0100] Reference example 2-6 A laminate was obtained in the same manner as in Reference Example 2-1, except that the aluminum alloy plate having an overhang made of ADC12 was used instead of the metal aluminum plate made of A1050, and the melamine resin-impregnated wooden board W3 (size: 10mm x 10mm x about 3mm) obtained in Preparation Example 3-1 was used instead of the melamine resin-impregnated wooden board W2. In this laminate, the thin plate containing melamine cured resin was well bonded to the rough surface of the aluminum alloy plate.
[0101] Reference example 2-7 A laminate was obtained in the same manner as in Reference Example 2-1, except that an aluminum alloy plate having an overhang made of AC4CH was used instead of the metal aluminum plate made of A1050, and a phenol resin-impregnated wooden board W4 (size: 10mm x 10mm x about 3mm) obtained in Preparation Example 3-2 was used instead of the melamine resin-impregnated wooden board W2. In this laminate, the thin plate containing the phenol cured resin was well bonded to the rough surface of the aluminum alloy plate.
[0102] Reference example 2-8 A laminate was obtained in the same manner as in Reference Example 2-1, except that the aluminum alloy plate having an overhang made of ADC12 was used instead of the metal aluminum plate made of A1050, and the precursor composition impregnated wooden plate W5 (size: 10mm x 10mm x about 3mm) obtained in Preparation Example 4-1 was used instead of the melamine resin impregnated wooden plate W2. In this laminate, the thin plate containing polyurethane resin was also well bonded to the rough surface of the aluminum alloy plate.
[0103] Reference examples 3-1~3-3 Laminates were obtained in the same manner as in Reference Examples 2-1, 2-3, and 2-4, except that the treatment method for the metal aluminum plate was changed from Method 1 to Method 3, and were designated Reference Examples 3-1, 3-2, and 3-3, respectively. When these laminates were visually observed, the thin plate containing the melamine cured resin and the metal aluminum plate were well bonded to each other.
[0104] 10. Adhesion between aluminum-containing roughened substrate and hardened layer formed from melamine resin-containing wood crushed material C1 One side of each of a plate (30 mm x 25 mm x 1.6 mm) made of metal aluminum (A1050) or a plate (30 mm x 25 mm x 5.0 mm) made of aluminum alloy (A6063) was subjected to electrical discharge machining based on the above method 2 to prepare two types of aluminum-containing roughened substrates. Then, using this aluminum-containing roughened substrate, melamine resin-containing crushed wood C1-1, C1-2 or C1-3, and a melamine resin-containing plate-shaped sample W6 (hereinafter referred to as "thickness-adjusting plate") prepared by the method described below, a bonded specimen was produced in this order, and a block shear test was performed to measure the compressive shear adhesive strength.
[0105] (Method of preparing melamine resin-containing plate-shaped sample W6) A melamine resin-containing plate-shaped sample W6 was obtained by carrying out the same operations as in Preparation Example 1-1, except that a cypress board (size: 30 mm (in the direction of the fibers) x 25 mm (in the direction perpendicular to the fibers) x 4 mm (thickness)) and a melamine resin aqueous solution obtained by diluting the melamine resin aqueous solution (1) with water to a solid content concentration of 10% by mass were used.
[0106] Test Example 1 The roughened aluminum alloy substrate (A6063) was placed on a hot plate preheated to 170°C with the rough surface facing up and heated. Next, about 1.5g of melamine resin-containing crushed wood C1-1 was evenly distributed on a portion (25mm x 25mm) of the rough surface, and two thickness adjustment plates were placed on top of each other and hot pressed (170°C, 3.1kN (5MPa), 5 minutes). After that, it was cooled to about 40°C to obtain a bonded specimen. Next, a block shear test was carried out according to the method of JIS K 6852. Specifically, the joint specimen was placed on a wood shear test fixture, and a load was applied to the wood material side with the aluminum substrate fixed at a test speed of 0.5 mm / min using a precision universal testing machine "AUTOGRAPH AG-X plus" (product name) manufactured by Shimadzu Corporation. 2 The maximum load (N) per unit area was measured and found to be 3.1 kN. The compressive shear adhesive strength (unit: MPa) was calculated using the following formula and found to be 7.8 MPa (see Table 1). Compressive shear adhesive strength = Maximum load / adhesive area
[0107] Test Example 2 A bonding specimen was prepared in the same manner as in Test Example 1, except that melamine resin-containing crushed wood material C1-2 was used instead of melamine resin-containing crushed wood material C1-1. The maximum load and compressive shear adhesive strength were measured and found to be 3.1 kN and 8.6 MPa, respectively (see Table 1).
[0108] Test Example 3 A bonding specimen was prepared in the same manner as in Test Example 1, except that melamine resin-containing crushed wood material C1-3 was used instead of melamine resin-containing crushed wood material C1-1. The maximum load and compressive shear adhesive strength were measured and found to be 3.1 kN and 9.6 MPa, respectively (see Table 1).
[0109] Test Example 4 A bonded specimen was prepared in the same manner as in Test Example 2, except that the press load during hot pressing was 1.0 kN (1.6 MPa). The maximum load and compressive shear adhesive strength were measured and found to be 1.0 kN and 8.1 MPa, respectively (see Table 1).
[0110] Test Example 5 A bonded specimen was prepared in the same manner as in Test Example 1, except that a roughened metal aluminum substrate (A1050) was used instead of the roughened aluminum alloy substrate (A6063). The maximum load and compressive shear bond strength were measured and found to be 3.1 kN and 9.4 MPa, respectively (see Table 1).
[0111] Test Example 6 A bonded specimen was prepared in the same manner as in Test Example 2, except that a roughened metal aluminum substrate (A1050) was used instead of the roughened aluminum alloy substrate (A6063). The maximum load and compressive shear bond strength were measured and found to be 3.1 kN and 8.0 MPa, respectively (see Table 1).
[0112] Test Example 7 A bonded specimen was prepared in the same manner as in Test Example 3, except that a roughened metal aluminum substrate (A1050) was used instead of the roughened aluminum alloy substrate (A6063). The maximum load and compressive shear bond strength were measured and found to be 3.1 kN and 9.9 MPa, respectively (see Table 1).
[0113] Test Example 8 A joint specimen was prepared in the same manner as in Test Example 1, except that instead of the melamine resin-containing crushed wood material C1-1, a crushed composite material (hereinafter referred to as "crushed material P") was used, which was obtained by kneading equal weights of wood flour with an outer diameter of approximately 200 μm or less that was not impregnated with resin and polypropylene resin. The maximum load and compressive shear adhesive strength were measured and found to be 3.1 kN and 3.6 MPa, respectively (see Table 1).
[0114] Test Example 9 A bonding specimen was prepared in the same manner as in Test Example 4, except that crushed material P was used instead of melamine resin-containing crushed wood material C1-2. The maximum load and compressive shear adhesive strength were measured and found to be 1.0 kN and 4.6 MPa, respectively (see Table 1).
[0115] Test Example 10 A bonding specimen was prepared in the same manner as in Test Example 5, except that crushed material P was used instead of melamine resin-containing crushed wood material C1-1. The maximum load and compressive shear adhesive strength were measured and found to be 3.1 kN and 6.8 MPa, respectively (see Table 1).
[0116] [Table 1]
[0117] As is clear from Table 1, the compressive shear adhesive strength to the aluminum substrate was large and a strong bond was obtained when the melamine resin-containing crushed wood materials C1-1, C1-2, or C1-3 were used, compared to when the crushed material P was used. In addition, no difference was observed in the effect of the melamine resin-containing crushed wood materials within the range of Test Examples 1 to 7, and it was confirmed that the crushed wood materials contribute to a strong bond as long as the size is such that the wood cell fibers are maintained. In addition, even when the pressing load was reduced to about one-third (pressing pressure: 1.6 MPa), the compressive shear adhesive strength was at the same level as when the pressing pressure was 5 MPa. [Industrial Applicability]
[0118] The composite of the present invention is a multilayer structure having a base containing aluminum and excellent structural stability, and can be suitably used as plates, frames, etc., or as building materials and architectural components, furniture and furnishings, vehicle components, home appliance parts, daily necessities, etc., with excellent appearance in the design layer. [Explanation of symbols]
[0119] 1: Complex 2: Base 4: Middle layer 6: Design layer 8: Overhang 9: Recessed part 10: Aluminum-containing roughened substrate
Claims
1. A composite body comprising an integrated body in which an aluminum-containing base and a decorative layer are joined via an intermediate layer, A composite body, characterized in that the intermediate layer is made of an aggregate of resin-impregnated wood pieces or a resin-impregnated wood board, and the surface of the base on the intermediate layer side has a plurality of overhang portions.
2. 2. The composite of claim 1, wherein the resin is also contained within the cell walls of the wood pieces or boards.
3. 2. The composite according to claim 1, wherein the resin is at least one selected from the group consisting of melamine resin, phenolic resin, urea resin, acrylic resin, styrene-based resin and urethane resin.
4. 2. The composite of claim 1, wherein the intermediate layer has a thickness of 0.1 to 20 mm.
5. 10. The composite of claim 1, wherein the decorative layer comprises a thin body of wood.
6. 2. The composite according to claim 1, wherein the overhang portion is formed by subjecting a surface of an article containing metallic aluminum or an aluminum alloy to an acid treatment, an electric discharge treatment, a shot blasting treatment, or an electrolytic etching treatment.
7. A method for producing the composite of claim 1, comprising the steps of: A process for producing an aluminum-containing roughened substrate by subjecting a substrate containing metallic aluminum or an aluminum alloy to an acid treatment, an electric discharge machining treatment, a shot blasting treatment, or an electrolytic etching treatment to form a plurality of overhang portions on a surface of the substrate; A step of crushing a resin component-impregnated wood obtained by impregnating wood with a resin component containing at least one selected from a precursor of a thermoplastic resin and a thermosetting resin to produce a resin component-containing crushed wood product; A step of placing the resin component-containing crushed wood material on a surface of the aluminum-containing roughened base material having the overhang portion to prepare a first load; A step of placing a design material on the resin component-containing crushed wood layer in the first load to prepare a second load; subjecting the second load to a hot press; A method for producing a composite, comprising:
8. The method for producing a composite body according to claim 7, wherein the thermoplastic resin is a urethane resin.
9. 8. The method for producing a composite body according to claim 7, wherein the thermosetting resin contains at least one selected from the group consisting of a melamine resin, a phenolic resin, and a urea resin.
10. The method for producing a composite body according to claim 7, wherein the major axis of the crushed wood material containing a resin component is 0.05 to 10 mm.
11. A method for producing the composite of claim 1, comprising the steps of: A process for producing an aluminum-containing roughened substrate by subjecting a substrate containing metallic aluminum or an aluminum alloy to an acid treatment, an electric discharge machining treatment, a shot blasting treatment, or an electrolytic etching treatment to form a plurality of overhang portions on a surface of the substrate; A step of producing a resin component-impregnated wooden board by impregnating a wooden board with a resin component containing at least one selected from a precursor of a thermoplastic resin and a thermosetting resin; A step of placing the resin component-impregnated wooden board on a surface of the aluminum-containing roughened base material having the overhang portion to prepare a third loaded object; A step of placing a design material on the resin component impregnated wooden board in the third load to create a fourth load; subjecting the fourth load to a hot press; A method for producing a composite, comprising:
12. The method for producing a composite body according to claim 11, wherein the thermoplastic resin is a urethane resin.
13. 12. The method for producing a composite body according to claim 11, wherein the thermosetting resin contains at least one selected from the group consisting of a melamine resin, a phenolic resin, and a urea resin.
14. The method for producing a composite body according to claim 11, wherein the resin component-impregnated wooden board has a thickness of 0.01 to 20 mm.
15. The method for manufacturing a composite body according to claim 7 or 11, wherein the decorative material comprises a thin-walled body of wood.
Citation Information
Patent Citations
Wooden decorative sheet and manufacture thereof
JP1991239543A
Curved surface moldable composite material by combination of resin-impregnated wood with lining material, and manufacture thereof
JP1998113906A
Surface treatment of metal and metallic member having surface obtained by this surface treatment method
JP1999293476A
Joint member, and manufacturing method of joint member
JP2021088059A
Non-flammable wood-based composite material and method of manufacturing the same
JP2022007386A